Job Insecurity According to the Mental Health of Workers in 25 Peruvian Cities during the COVID-19 Pandemic - Palomino-Ruiz, Nataly (2022)
The pandemic brought various problems among workers, one of them being job insecurity, since many lost their jobs and others had the possibility of being fired, which could influence their mental health. The aim of this analytical cross-sectional study was to determine the relationship between job insecurity and mental health among workers in 25 Peruvian cities during the COVID-19 pandemic. Previously validated surveys were used to inquire about job insecurity and three mental health disorders (depression, anxiety, and stress) as well as other variables. Of the 1855 workers, 14% had moderate or higher levels of stress, 30% had anxiety, and 16% had depression. Having had job insecurity was associated with moderate or higher levels of depression (RPa: 1.71; 95% CI: 1.51–1.94; p-value < 0.001), anxiety (RPa: 1.43; 95% CI: 1.25–1.64; p-value < 0.001), and stress (RPa: 1.77; 95% CI: 1.41–2.22; p-value < 0.001). Depression was also associated with having been fired during the pandemic and associated with eight professions. Anxiety was associated with being a man and having been fired, while stress was associated with three professions. There is a clear association between having job insecurity and suffering from the three mental pathologies evaluated, which highlights the importance of assessing the mental impact.